PENGARUH SANKSI PAJAK, KUALITAS PELAYANAN, TINGKAT PENDIDIKAN TERHADAP KEPATUHAN WAJIB PAJAK UMKM (Survei Pedagang di Pusat Grosir Solo) - Hasanah, Uswatun; Suharno, Suharno; Widarno, Bambang (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2019)
The purpose of this study is to analyze the effect of tax sanctions, service quality, and level of education. This study uses a survey method, the type of data used is qualitative data that will be supported with quantitative data, data sources used primary data and secondary data. The population in this study were 150 MSME taxpayers from 700 traders at the Solo Wholesale Center. The number of samples in the study was 50 respondents, with sampling using a Convenience Sampling (sample selected with consideration of convenience). Data collection methods used: questionnaires and interviews. Data analysis techniques used were validity test, reliability test, classic assumption test, and multiple linear regression analysis, t test, F test, and determination coefficient test by using SPSS version 21. The results of the study concluded that: 1). There is a significant influence between tax sanctions on SME taxpayer compliance with traders at the Solo Wholesale Center 2). There is a significant influence on the quality of service to the compliance of SME merchant tax wages in Solo Wholesale Center 3) There is an influence of education level on MSME taxpayer compliance at the Wholesale Center Solo.From the calculation results obtained the value of Adjusted R Square =0,395 = 39,5% so that it is known that the influence / contribution given by the independent variable is Tax Sanctions (XÂ¬1), Service Quality (X2) and Education Level (X3) towards the dependent variable is the MSME Taxpayer Compliance (Y) on Traders at PGS of 39,5% while the rest (100% - 39,5%) = 60,5% is influenced by other factors outside the variables not examined.